Increasing Sales of Confectionery Products Produced by MSMEs in Majalaya, Bandung Regency, West Java, Through Online Marketing - Putra, Deva; Saefullah, Rifki (Research Collaboration Community (Rescollacom), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a sector that significantly contributes to spurring Indonesia's economic growth. This is due to their large labor absorption capacity and proximity to the common people. However, MSMEs in Indonesia still face various challenges, including promotion, marketing, and sales of their products. Along with the development of information and communication technology, online marketing and sales have been utilized. Online product sales and marketing have many advantages, including broad reach, agility, and accessibility. Therefore, this paper examines efforts to increase sales of confectionery products produced by MSMEs in Majalaya, Bandung Regency, West Java, through online marketing. Qualitative research was conducted using various data collection procedures to deepen understanding and ensure the reliability of the collected data. The goal was to gain in-depth and rich insights into a phenomenon within MSMEs in Majalaya. The research indicates that MSMEs in Majalaya, like many others, need to improve online marketing to increase sales and competitiveness.